Firm-level antecedents of export performance - Keskin, Ayşe Hande. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Removal of barriers to international trade and investment in addition to technological developments particularly in communication and digitalization increased the significance of global trade in 2000s. However, recent developments regarding UK’s Brexit uncertainty and potential trade wars have been threatening the international business activities. Changing nature of the trade dynamics and conditions of competition raises the importance of exporting especially for developing economies. In this context, Turkey, as a developing economy, is in need to build a sustainable economy by increasing competitive power and managing chronic account deficit. In this study, firm-level antecedents of export performance are investigated. The resource-based view, which emphasizes the internal environment of the firm as the source of its competitive advantage, establishes the theoretical framework of the study. The sample is drawn from Istanbul Chamber of Industry’s “Turkey’s Largest 1000 Manufacturing Firms” list and includes 58 firms. Data were collected from archival sources as well as through a survey. Research findings show that manager’s level of education, foreign language ability, and level of motivation for exporting as well as firm’s export marketing strategies and organizational export commitment differentiate between firms with better and poorer export performance. However, regression analysis reveals manager’s level of motivation for exporting as the most significant antecedent of export performance.
Keywords: Export marketing.